1993
DOI: 10.1523/jneurosci.13-12-05356.1993
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal fluctuations in brain nuclei in the red-sided garter snake and their hormonal control

Abstract: In many vertebrates, breeding seasons are protracted and mating behavior is temporally associated with gonadal growth and increased sex steroid hormone secretion. In the red-sided garter snake (Thamnophis sirtalis parietalis), mating behavior is restricted to the 2-4 weeks immediately following emergence from winter dormancy. During this period mating behavior is sex-specific: chin-rubbing is exhibited only by males and receptivity to chin-rubbing is exhibited only by females. It is remarkable that mating occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…T and/or breeding environmental conditions enhance male sexual behavior and in parallel enhance volume and/or soma size of the POA and AMY in Japanese quail, whiptail lizards and rodents [22,24,25,27,62,71,82,87,90,91]. Interestingly, as in the present study, a seasonal environmental cue (photoperiod) influences the response of a portion of the AMY (the MeApd) to T in Siberian hamsters.…”
Section: Reproductive Behavior and Morphology In Other Speciessupporting
confidence: 71%
“…T and/or breeding environmental conditions enhance male sexual behavior and in parallel enhance volume and/or soma size of the POA and AMY in Japanese quail, whiptail lizards and rodents [22,24,25,27,62,71,82,87,90,91]. Interestingly, as in the present study, a seasonal environmental cue (photoperiod) influences the response of a portion of the AMY (the MeApd) to T in Siberian hamsters.…”
Section: Reproductive Behavior and Morphology In Other Speciessupporting
confidence: 71%
“…Other results in fear context conditioning have showed that lesions of the dorsomedial telencephalic portion in Betta splendens produced a facilitation of habituation to the context (Marino-Neto & Sabbatini, 1983) and variations in levels of aggression (de Bruin, 1980). Taken as a whole, these data indicate that the Dm telencephalon area shares a great similarity with pallial amygdaloid nuclei and homologous structures in reptiles (Crews et al, 1993;Keating et al, 1970;Krohner & Crews, 1987;Tarr, 1977), birds (Cohen, 1975;Dafter, 1975;Ikebuchi et al, 2009;Martínez-García, et al, 2002;Phillips 1968;Phillips & Youngren, 1968;Vowles & Beasley, 1974;Zeier, 1971), and mammals (Ambrogli et al, 1991;Fonberg, 1973;Grossman et al, 1974;Hanwerker et al, 1974;Horvath, 1963;Killcross et al, 1997;Liang & McGaugh, 1983;McIntery & Stein, 1973;Pellegrino, 1968;Roozendaal et al, 1993;Sanchez-Riolobos, 1986;Takashina et al, 1995;van-der-Zee et al, 1997;Werka et al, 1978;Wiersma et al, 1998). These amygdala lesions affect not only the avoidance conditioning, but also the fear conditioning in mammals and birds (Cohen, 1975;Dafter, 1976).…”
Section: Function Of the Amygdala Homologous In Non Mammals Vertebratessupporting
confidence: 51%
“…These data coupled with the effects of Dm lesions on aggressive behavior, breeding, habituation in situations of aggression in a resident/intruder paradigm (de Bruin, 1980;Marino-Neto & Sabbatini, 1983), as well as data from electrical stimulation of Dm in Carassius that show facilitation and inhibition of aggressive and reproductive patterns or startle response and escape (Savage, 1971), support the homology of the fish telencephalic Dmv with the pallial amygdala of mammals. This idea have been proposed on the basis of neuroanatomical and neurohistochemical evidence of similarities between the two structures developing an evolution-based model of brain organization (Braford, 1995;Echteler & Saidel, 1981;Hornby et al, 1987;Ito et al, 1986;Medina & Reiner, 1995;Murakami et al, 1983;Northcutt, 1995;Piñuela & Nortcutt, 1994;Reiner & Northcutt, 1992;Striedter, 1991;Wulliman & Rink, 2002) and that of reptiles (Crews et al, 1993;Keating et al, 1970;Krohner & Crews, 1987;Tarr, 1977), birds (Cohen, 1975;Dafter, 1975;Ikebuchi et al, 2009;Phillips 1968;Phillips & Youngren, 1968;Vowles & Beasley, 1974;Zeier, 1971), and mammals (Ambrogli et al, 1991;Fonberg, 1973;Grossman et al, 1974;Hanwerker et al, 1974;Horvath, 1963;Killcross et al, 1997;Liang & McGaugh, 1983;McIntery & Stein, 1973;Pellegrino, 1968;Roozendaal et al, 1993;…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…I chose two brain regions for this analysis that are both seasonally variable and sexually dimorphic: the medial cortex and NS (Holding et al, 2012;Kabelik et al, 2006;Krohmer et al, 2011;Crews et al, 1993). Because only NPY cells, and not AVT cells, occur in the medial cortex and NS, I distinguished the boundaries of these regions using the same brain atlas used for counting NPY cells Krohmer et al, 2010;Martínez-Marcos et al, 2001), and then outlined the region of interest and measured its area using the calibrated measure feature of ImageJ software (NIH); I repeated this procedure for every tissue section containing the region of interest.…”
Section: Normalization Of Sexual Size Dimorphism For Direct Sex Compamentioning
confidence: 99%